Analisis Beban Kerja Perawat Pelaksana di Ruang Rawat Inap di RSU Bahteramas Sulawesi Tenggara - Iqra S; Rusna Tahir (Politeknik Kesehatan Kemenkes Mamuju, 2020)
The quality of health services, one of which is determined by the quality of nursing services provided to patients. However, the workload problems felt by nurses both qualitatively and quantitatively often lead to a decrease in the quality of nursing care services that are sometimes not noticed by the organization. This study aims to analyze the differences in the workload of nurses working in class I, class II, and class III care rooms. The study was observational analytic with cross sectional study approach. Samples were taken as many as 74 female nurses who worked â‰¥ 2 years in the wards class, and the samples were taken by purposive sampling. Data collection is done through questionnaires, observations, and interviews. Data were analyzed by Kruskal Wallis analysis to see differences in workload from the three treatment rooms. The results showed a significant difference in workload between the three wards class (p = 0.037), where class III treatment rooms had a greater workload compared to other treatment rooms (Mean rank = 45.81). The need for an analysis of the needs of nurses is adjusted to the level of dependence of patients in each room. So the workload received by nurses in accordance with existing conditions.